Buildthermo: an algorithm for visualizing building heat dynamics / Amira Shazlin Adnan ... [et al.] - Adnan, Amira Shazlin; Che Ani, Adi Irfan; Mohd Pahroraji, Mohamad Ezad Hafez; Ayob, Mohd Asraf; Wahi, Noraziah (2024)
This paper introduces BUILDthermo, a groundbreaking approach that transforms the analysis of building heat dynamics through advanced algorithms and visualization techniques. By integrating microclimate data, building characteristics, and urban attributes, BUILDthermo provides holistic insights into the thermal conditions of building surroundings. Our innovative algorithm is rigorously developed and validated, delivering precise assessments and facilitating informed decision-making in urban development. With an intuitive interface, BUILDthermo empowers stakeholders to visualize and interpret building heat data effortlessly. Users can explore scenarios, evaluate design alternatives, and optimize outdoor environments for comfort and sustainability. The methodology details, including parameter considerations and algorithmic processes, are outlined. Case studies demonstrate the practical application and efficacy of BUILDthermo in real-world urban settings. As a significant advancement, BUILDthermo offers a powerful tool for urban planners, architects, and environmental engineers to create more livable and sustainable cities. This research contributes valuable insights to urban climate resilience and human-centric design.